Universal HIV screening in the emergency department: an interrupted time series analysis. (1st September 2022) - Ford, James S.; Rouleau, Samuel G.; Voong, Stephanie; Morgan, Brittany; Toosi, Kavian; Waldman, Sarah; Meng, Zichun; Chechi, Tasleem; Tran, Nam; May, Larissa
Abstract : We performed a calendar-matched, 12-month, before (November 27, 2017 to November 26, 2018) and after (November 27, 2018 to November 26, 2019) study, to assess the utility of an emergency department-based HIV screening program. There were 710 and 14 335 patients screened for HIV during the pre and post-best practice alert (BPA) periods, respectively, representing more than a 20-fold increase in HIV screening following BPA implementation. Total HIV positive tests increased 5-fold following BPA implementation.